2018
DOI: 10.2139/ssrn.3307903
|View full text |Cite
|
Sign up to set email alerts
|

Financial Inclusion: Concepts, Issues and Policies for India

Abstract: This paper lays out some of the basic concepts surrounding financial inclusion, including access to banking, digital payments and financial literacy, as well as markets for health insurance, crop insurance, agricultural credit, small firm finance, and microcredit/ microfinance. It goes on to discuss various empirical and institutional studies of these dimensions of financial inclusion in the context of developing countries. The paper then outlines several recent studies for India sponsored by the International… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 123 publications
0
9
0
Order By: Relevance
“…Most respondents are involved in the household's decision about where and how much to save, and a majority trusts both the BCSA and banks. 8 In terms of time preferences, 42 percent of the participants are impatient, i.e., they prefer money today instead of a larger amount in one week. The average distance from the house to the BCSA is about 290 meters as a crow flies.…”
Section: E Baseline Characteristics and Balance Checkmentioning
confidence: 99%
See 1 more Smart Citation
“…Most respondents are involved in the household's decision about where and how much to save, and a majority trusts both the BCSA and banks. 8 In terms of time preferences, 42 percent of the participants are impatient, i.e., they prefer money today instead of a larger amount in one week. The average distance from the house to the BCSA is about 290 meters as a crow flies.…”
Section: E Baseline Characteristics and Balance Checkmentioning
confidence: 99%
“…Castes are classified in the following categories: ST (Scheduled Tribe), SC (Scheduled Caste), OBC (Other Backward Caste), and FC (Forward Caste) 8. The respondents were asked whether they trust the BCSA and banks.…”
mentioning
confidence: 99%
“…The move from focusing on the institution to focusing on individuals meant moving the focus from the supply side to the demand side (Copestake, 2019; Duvendack & Mader, 2019; Singh, 2018; Zhang & Posso, 2019). The results of the Findex surveys in 2011, 2014, and 2017 (Demirgüç‐Kunt, Klapper, Singer, Ansar, & Hess, 2018; Demirguc‐Kunt, Klapper, Singer, & Oudheusden, 2015) allow us to see if individuals are now getting financially included .…”
Section: Financial Inclusionmentioning
confidence: 99%
“…The ability of customers making sound financial decisions is important in developing a strong personal savings that is important in efficient allocation of resources leading to financial stability. Singh (2017) in his exploratory research of financial literacy and stability in India found out that apart from exposure to fraud and abuse, inadequate education on financial matters might lead to borrowers' behavior that intensifies financial fragility. Literate customers will exercise innovative-enhancing demand on the financial system and improve monitoring in the financial market leading to improved transparency and stability in the financial system (Fomum and Jesse, 2017;Hall, 2008;Soskic, 2011).…”
Section: Previous Evidencementioning
confidence: 99%